Penerapan Model Pembelajaran TGT (Team Games Tournament) Untuk Meningkatkan Hasil Belajar Kelas II SD - Istikhah Istikhah; Iqnatia Alfiansyah; Nanang Khoirul Umam (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Based on the results of the analysis that has been carried out, it shows that students' learning outcomes in mathematics have increased. This is indicated by the increase in the class average score, namely at the time of pre-action 51.63 increased to 85.90 in cycle I then increased again in cycle II to 89.09. From the observation data obtained before carrying out the action, students seemed less active in learning. After being given action students look more active both in question and answer activities and during group activities.